Flexible or rigid? Evidence on managerial ability and cost structure - Banker, Rajiv D.; Huang, Rong; Wang, Yuxuan; Yan, Yan (Contemporary Accounting Research, 2025)
Abstract This study investigates the association between managerial ability and cost rigidity. Cost rigidity refers to the relative proportion of fixed and variable costs. We expect that high‐ability managers will assess the potential upside congestion and downside default risks and choose an appropriate level of cost rigidity accordingly. Our results show that, on average, high‐ability managers tend to adopt a more rigid cost structure because they are more likely to realize favorable demand, and therefore, they retain higher capacity with more fixed inputs to alleviate potential congestion risk. We further document that firms with high‐ability managers will exhibit a higher (lower) level of cost rigidity when facing higher congestion risk (default risk). Our results are robust to using a propensity score matching method, a CEO turnover subsample, and alternative measures of cost rigidity and managerial ability. Taken together, this study suggests that firms' capacity management choices vary with the level of managerial ability.